2019
DOI: 10.1111/1365-2478.12883
|View full text |Cite
|
Sign up to set email alerts
|

Probing crustal anisotropy by receiver functions at the deep continental drilling site KTB in Southern Germany

Abstract: Seismic anisotropy is a unique observational tool for remotely studying deformation and stress within the Earth. Effects of anisotropy can be seen in seismic data; they are due to mineral alignment, fractures or layering. Seismic anisotropy is linked to local stress and strain, allowing modern geophysics to derive geomechanical properties from seismic data for supporting well planning and fracking. For unravelling anisotropic properties of the crust, the teleseismic receiver functions methodology has started t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…Because the mineral assemblages of the phyllite samples analyzed in this study correspond to typical greenschist-facies minerals of a pelitic protolith (biotite zone [67]), it is suggested that the calculated seismic properties reflect a part of the observed seismic anisotropies in the highly deformed middle crustal zone. Tectonic processes during compressive or extensional regimes in the middle and lower crust result in ductilely deformed planar structures aligned subnormal to compressive or extensional stress, inducing strong seismic anisotropies when the rocks are rich in mica and/or amphibole [5,18,20,22,60,109]. It is particularly important below the depth of microcrack closure (approximately 200-250 MPa [15,16,18]), where the plastically deformed shear fabrics and aligned minerals play an important role in controlling the seismic properties.…”
Section: Implications For Seismic Anisotropy In Continental Crustmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the mineral assemblages of the phyllite samples analyzed in this study correspond to typical greenschist-facies minerals of a pelitic protolith (biotite zone [67]), it is suggested that the calculated seismic properties reflect a part of the observed seismic anisotropies in the highly deformed middle crustal zone. Tectonic processes during compressive or extensional regimes in the middle and lower crust result in ductilely deformed planar structures aligned subnormal to compressive or extensional stress, inducing strong seismic anisotropies when the rocks are rich in mica and/or amphibole [5,18,20,22,60,109]. It is particularly important below the depth of microcrack closure (approximately 200-250 MPa [15,16,18]), where the plastically deformed shear fabrics and aligned minerals play an important role in controlling the seismic properties.…”
Section: Implications For Seismic Anisotropy In Continental Crustmentioning
confidence: 99%
“…Tectonic processes during compressive or extensional regimes in the middle and lower crust result in ductilely deformed planar structures aligned subnormal to compressive or extensional stress, inducing strong seismic anisotropies when the rocks are rich in mica and/or amphibole [5,18,20,22,60,109]. It is particularly important below the depth of microcrack closure (approximately 200-250 MPa [15,16,18]), where the plastically deformed shear fabrics and aligned minerals play an important role in controlling the seismic properties.…”
Section: Implications For Seismic Anisotropy In Continental Crustmentioning
confidence: 99%
See 1 more Smart Citation
“…Our aim was to select the best-fitting model by minimizing the misfit of all estimated parameters. To assess reliability, we calculated the standard deviation of model parameters from an ensemble of models with misfits less than 1.1 times of the misfit of the best-fit model (Bianchi & Bokelmann, 2019).…”
Section: Neighborhood Algorithm Inversionmentioning
confidence: 99%
“…Local S-wave polarization properties along northwestern segments of the NAFZ suggests that both stress-and structure induced mechanisms cause seismic anisotropy in the upper 8-10 km of the crust (Eken, Bohnhoff, et al, 2013;Hurd & Bohnhoff, 2012). The joint interpretation of receiver function analyses (e.g., harmonic decomposition, and NA-based receiver functions modeling), for instance, can reveal the actual orientation and geometry of anisotropic structures at various depths of the crust and uppermost mantle (Bianchi & Bokelmann, 2019;Frederiksen & Bostock, 2000;Licciardi & Piana-Agostinetti, 2016). Licciardi et al (2018) reported an asymmetry in the variation of crustal anisotropy parameters across the central NAFZ using a harmonic decomposition approach that exploits directional dependence of receiver functions.…”
Section: Introductionmentioning
confidence: 99%